2015
DOI: 10.1097/aog.0000000000001066
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Tetanus Toxoid, Reduced Diphtheria Toxoid, and Acellular Pertussis and Influenza Vaccinations in Pregnancy

Abstract: Objective To evaluate the safety of co-administering tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Tdap) and influenza vaccines during pregnancy by comparing adverse events after concomitant and sequential vaccination. Methods We conducted a retrospective cohort study of pregnant women aged 14–49 years in the Vaccine Safety Datalink from January 1, 2007 to November 15, 2013. We compared medically attended acute events (fever, any acute reaction) and adverse birth outcomes (preterm deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 22 publications
5
73
0
Order By: Relevance
“…Another observational study of 36,844 pregnancies in the US showed that acute adverse events were rare following concomitant vaccination and there was no difference in preterm delivery, low birth weight, or SGA births among women who received pertussis and seasonal influenza vaccine concomitantly. 40 These studies suggest concomitant vaccination is safe; however, additional research is needed, particularly with regards to pregnancy outcomes.…”
Section: Recommendations For Future Research and Surveillance Of Matementioning
confidence: 99%
See 2 more Smart Citations
“…Another observational study of 36,844 pregnancies in the US showed that acute adverse events were rare following concomitant vaccination and there was no difference in preterm delivery, low birth weight, or SGA births among women who received pertussis and seasonal influenza vaccine concomitantly. 40 These studies suggest concomitant vaccination is safe; however, additional research is needed, particularly with regards to pregnancy outcomes.…”
Section: Recommendations For Future Research and Surveillance Of Matementioning
confidence: 99%
“…[39][40][41][42] Between 1-11% of pregnant women report pain or swelling at the injection site, and between 2-3% of women report a fever following vaccination. 39,42,43 However, one prospective study reported as many as 79% of pregnant women experiencing pain or swelling at the injection site.…”
Section: Acellular Pertussis Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of adverse effects of vaccination and obstetric adverse effects were evaluated, concluding that coadministration of vaccines had no higher incidence of severe adverse events in vaccination or in the development of preterm delivery, small for gestational age, versus patients who received administration sequentially 29 . A retrospective study of same authors measured the risk of acute adverse events and adverse events at birth in women receiving Tdap vaccine during pregnancy, and who had previously received tetanus vaccine.…”
Section: Effectiveness and Safety Of Tdap Antenatal Vaccinementioning
confidence: 99%
“…The safety of influenza and pertussis vaccines is very good, and they can be administered at the same consultation. 3 Close household contacts and carers such as siblings, partners and grandparents should also be up to date with all of their age-appropriate immunisations, such as rotavirus, varicella and MMR (measles-mumpsrubella) and particularly pertussis vaccine.…”
Section: Recommendations For Pregnant Womenmentioning
confidence: 99%